2021
DOI: 10.1097/cmr.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic acral melanoma treatment outcomes: a systematic review and meta-analysis

Abstract: Acral melanomas are a unique subset of melanomas occurring on the palms, soles, and nails. There is poor prognosis with surgery alone and no specific guidelines for the treatment of metastatic acral melanoma. This meta-analysis explored the systemic therapy outcomes for metastatic acral melanoma. Medline, Pubmed, EMBASE, and the grey literature were searched from 2010 to August 2020 for studies specifying the treatment outcome of metastatic acral melanoma. Studies were assessed by two investigators. A random-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…A meta-analysis of studies on the treatment of metastatic acral melanoma with checkpoint inhibitors showed an objective response rate of 20%, which is significantly higher than with chemotherapy. In acral melanoma, treatment with anti-PD-1 (n Z 330) was associated with significantly better OS at 12 months (53%) than patients treated with anti-CTLA-4 therapies (n Z 94) (34% survival at 12 months, P < 0.001) [192]. The combination therapy of anti-CTLA-4 and anti-PD-1 immunotherapy showed increased efficacy with an objective response rate of 43% as compared to singleagent therapy [193].…”
Section: Acral Melanomamentioning
confidence: 98%
“…A meta-analysis of studies on the treatment of metastatic acral melanoma with checkpoint inhibitors showed an objective response rate of 20%, which is significantly higher than with chemotherapy. In acral melanoma, treatment with anti-PD-1 (n Z 330) was associated with significantly better OS at 12 months (53%) than patients treated with anti-CTLA-4 therapies (n Z 94) (34% survival at 12 months, P < 0.001) [192]. The combination therapy of anti-CTLA-4 and anti-PD-1 immunotherapy showed increased efficacy with an objective response rate of 43% as compared to singleagent therapy [193].…”
Section: Acral Melanomamentioning
confidence: 98%
“… 17 , 18 , 43 This difference in the response rate could be attributed to nivolumab and ipilimumab (both immune checkpoint inhibitors) that were administered as prior therapies in some patients, suggesting the possibility of including nonresponders who were switched in this survey and the substantially lower incidence of acral melanoma and mucosal melanoma in both small‐ and large‐scale international clinical studies. 13 , 44 However, DCR (51.9%) in the RECIST assessment set of this survey was comparable with that in the pembrolizumab phase 3 KEYNOTE‐006 trial (DCR [CR + PR + SD]: 47.6% [q2w] and 46.9% [q3w]). 17 , 18 , 43 The lower ORR observed in this survey (compared with KEYNOTE‐006 studies) could also be attributed to a patient performance status (ECOG PS) of 2/3, as these patients were nonresponders in the real‐world setting in Japan.…”
Section: Discussionmentioning
confidence: 52%
“…The response rate was lower compared with that in the KEYNOTE‐006 development program (pembrolizumab administered once every 2 weeks [q2w] [36.9%] and q3w [36.1%] vs ipilimumab [11.9%]) 17,18,43 . This difference in the response rate could be attributed to nivolumab and ipilimumab (both immune checkpoint inhibitors) that were administered as prior therapies in some patients, suggesting the possibility of including nonresponders who were switched in this survey and the substantially lower incidence of acral melanoma and mucosal melanoma in both small‐ and large‐scale international clinical studies 13,44 . However, DCR (51.9%) in the RECIST assessment set of this survey was comparable with that in the pembrolizumab phase 3 KEYNOTE‐006 trial (DCR [CR + PR + SD]: 47.6% [q2w] and 46.9% [q3w]) 17,18,43 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations